Management of the Human Capital as the Factor of Increase in Profitability of the Capital of the Oganization (Путеводитель предпринимателя, 2020)
In the article approaches to definition of the concepts of the capital and the human capital are considered. The interrelation between practices of management of the human capital and efficiency of activity of the organization is revealed.